System of systems method and formal function decomposition for software systems - LU Han-hua; ZHANG Shun-yi; WANG Ya-shi; MIN Li-juan (Tongxin xuebao)
Based on the theory and method of system of system（SoS）,the research work for the formal functional de-composition and estimation of large scale and open software systems was described,which were often emerged in IOT（internet of things） and cloud computing environments.It was proposed that abstraction description was necessary for the SoS properties of a large scale and open software system.Based on system abstract,formal methods for functional decomposition and estimation were described.The applications of the methods in system development and stable inter-mediate form building were discussed.The methods proposed here are helpful for improving the processes of implemen-tation,deployment and maintenance of large scale and open software systems in IOT and cloud computing environments.